Assessment of Workplace Safety Climate among Healthcare Workers: A Case Study of the Public Sector Hospitals in Greece - Olympia Christofilea; Georgios Farantos; Loukia Psaridi; Maria Tsaousi; Sofia Sartzi; Georgios Dounias (European Scientific Journal, ESJ, 2024)
Safety climate assessment is considered an effective tool to investigate employees' perceptions of workplace safety practices, attitudes, and behaviors. Scope and Aims: The purpose of the survey is to assess the climate of workplace safety among employees in the public healthcare sector, with the following objectives: a) to identify the most decisive factors that determine the climate of safety at work in order to prioritize interventions, and b) to subserve commitment to create a positive climate of safety among both management and employees. Methods: For this purpose, a cross-sectional study was conducted in 23 hospitals, which concerned all employees in total. The tool used was the Nordic Occupational Safety Climate Questionnaire (NOSACQ-50). Results: The results showed that the safety climate was generally negative and that there was a need for interventions (minor or major). Parameters with high statistical variation (< 0.0001) were identified, such as working position (employee or leader), employment status (tenure), age, hospital of origin, and specialty of the employee. Conclusion: To address the gaps identified, efforts need to be made to promote an effective and positive safety climate in all hospitals in the study, to emphasize prevention, and to strengthen the commitment of both management and employees in this direction.